Wind tunnel test of a rotorcraft with lift compounding - Bauknecht, A.; Wang, X.; Chopra, I. (My University, 2019)
A recent doctrine in rotorcraft development is the pursuit of higher flight speeds. Limiting factors are compressibility effects on the advancing blade side and decreasing lift potential on the retreating blade side. It may therefore be beneficial to employ a hingeless rotor to generate additional lift on the advancing blade side and compensate the resulting rolling moment with a fixed-wing on the retreating blade side. This concept is a form of “lift-compounding” that has not been studied in detail yet. The present paper presents results of a wind tunnel test with a slowed, hingeless rotor and single fixed-wing (0.7R span, 0.24R below rotor plane) on the retreating blade side. Based on rotor test stand data and flow field measurements, the impact of operational and rotor parameters on performance and flow field of the system is examined, mutual interaction effects between rotor and fixed-wing are analyzed, and dominant flow structures are characterized in the reverse flow region on the retreating blade side. Flow field analysis reveals a dynamic stall vortex that freely convects through the reverse flow region and rivals the blade tip vortices in strength. Contrary to previous beliefs, this vortex originates from upstream of the reverse flow region and only its detachment from the rotor blade is related to entering this region. Advance ratio and shaft tilt angle are found to have significant and non-linear impact on the dynamic stall vortex and its interactions with rotor blades and other vortices. The rotor downwash reduces fixed-wing lift by up to 23% and increases its vibratory loads, while the fixed-wing is found to influence the effective angle of attack of the retreating rotor blade by up to 2 deg. The combination of finite rolling moment trim and aft shaft tilt increases the rotor lift coefficient by up to about 79% at 6 deg rotor collective and the corresponding peak lift-to-drag ratio of the compound rotorcraft is improved by up to 60% at ? = 0.5. Results are compared with predictions from a comprehensive rotor analysis code that is expanded to cover the main effects of added fixed-wing and is able to reproduce general performance trends of the rotorcraft. The present study highlights that adding a single fixed-wing to a high-speed hingeless rotor could significantly improve its performance.